The Characteristics of Sports Injuries in Adolescent Athletes according to Sports Specialization: A Preliminary Study - Seong-Keun Hong; Jong-jin Park (Asian Society of Kinesiology, 2024)
OBJECTIVES The purpose of this study is to investigate the characteristics of sports injuries in adolescent athletes according to sports specialization. METHODS One hundred and seventeen adolescent athletes including soccer, swimming, artery, weightlifting, modern pentathlon, and softball were recruited for this study, and a 12 questionnaire related to sports injuries was surveyed and analyzed. RESULTS The longer the period of sports specialization, the more frequent the number of sports injuries. Most sports injuries occur in the afternoon, but some adolescent athletes with long careers have had injuries in the early morning. Adolescent athletes with less than 3 years of careers had the highest incidence of sports injuries during match(52%), while those with 3 to 5 years (55%) of careers and more than 5 years (73%) of careers had the highest incidence of injuries during training. The main causes of sports injuries for athletes with less than 3 years of careers were poor skill (27%), overuse (25%), and lack of warm-up (23%). For adolescent athletes with 3 to 5 years of careers, the main causes were poor skill (31%), lack of warm-up (19%), and overuse(16%). 5 years or more of careers, the main causes were poor skill (35%), overuse (24%), and lack of warm-up (19%). CONCLUSIONS Adolescent athletes who are exposed to sports specialization early may be exposed to sports injuries due to intensive training, overuse, and poor skill according to the characteristics of the sport. Therefore, managers such as coaches and athletic trainers need to create a training environment to prevent sports injuries due to sports specialization of adolescent athletes.